Knowledge Based Networking - KEENEY, JOHN; LEWIS, DAVID; O'SULLIVAN, DECLAN; JONES, DOMINIC HUGH; SONG, GUO (IGI Global, 2009)
Knowledge-Based Networking, which is built on-top of Content-based Networking (CBN), involves the forwarding of events across a network of brokers based on subscription filters applied to some semantics of the data and associated metadata of the events contents. Knowledge-based Networks (KBN) therefore support the efficient filtered dissemination of semantically enriched knowledge over a large, loosely coupled network of distributed heterogeneous agents. This is achieved by incorporating ontological semantics into event messages, allowing subscribers to define semantic filters, and providing a subscription brokering and routing mechanism. The KBN used for this work provides ontological concepts as an additional message attribute type, onto which subsumption relationships, equivalence, type queries and arbitrary ontological relationships can be applied. It also provides a bag type to be used that supports bags equivalence, sub-bag and super-bag relationships to be used in subscription filters, composed with traditional CBN subscription operators or the ontological operators. When combined with the benefits of Content?based Networking, this allows subscribers to easily express meaningful subscription interests and receive results in a more expressive and flexible distributed event system than heretofore. Within this chapter the detailed analysis of ontological operators and their application to a publish/subscribe (pub/sub) domain will be fully explored and evaluated.
Handbook of Research on Advanced Distributed Event-Based Systems, Publish-Subscribe and Message Filtering Technologies (Principles and Applications of Distributed Event-Based Systems)
PUBLISHED
New York
Keywords: Computer Science